2021
DOI: 10.1088/1742-6596/1806/1/012193
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitude profile towards chemistry based on Research-Oriented Collaborative Inquiry Learning Model (REORCILEA)

Abstract: Scientific attitude is one of the important attitudes that can support the learning of chemistry. Scientific attitude can make students more active in learning students will be more curious that is related to student achievement. The sample of this study is 66 senior high school students as participants who apply the Research-Oriented Collaborative Inquiry Learning model. The questionnaire was validated with person reliability item reliability and item fit in good category. The results showed that most student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In this model, students are required to develop ideas through several scientific steps such as promoting ideas, asking questions, explaining phenomena, and connecting learning (Irwanto, 2022). The effectiveness of the REORCILEA towards scientific attitudes is evidenced by previous studies such as the student who applies REORCILEA in learning had a high score for scientific attitude, so REORCILEA effectively improve students' scientific attitude (Huda and Rohaeti, 2021).…”
Section: Results Of Instructional Methods Themementioning
confidence: 99%
“…In this model, students are required to develop ideas through several scientific steps such as promoting ideas, asking questions, explaining phenomena, and connecting learning (Irwanto, 2022). The effectiveness of the REORCILEA towards scientific attitudes is evidenced by previous studies such as the student who applies REORCILEA in learning had a high score for scientific attitude, so REORCILEA effectively improve students' scientific attitude (Huda and Rohaeti, 2021).…”
Section: Results Of Instructional Methods Themementioning
confidence: 99%
“…(Buchanan et al, 2016) Scientific attitude, being one of the important attitudes that can support the learning of chemistry, for example, makes students more active in learning and elicits curiosity that is related to achievement. (Huda & Rohaeti, 2021) That study found that using an inquiry model provided more experience for students and that scientific attitude can improve for better learning achievement. Research has shown though that expectation of better attitudes from students (as a result of exposure to inquirybased practices) are not always as apparent when viewed through the lenses of its other affordances.…”
Section: Potential Benefits Of Ibl On Student Attitudementioning
confidence: 95%